Early elevated alkaline phosphatase increases the risk of large-for-gestational-age birth weight in pregnant women with normal glucose tolerance. (July 2018) - Liu, Yingfeng; Hou, Wolin; Meng, Xiyan; Zhao, Weijing; Pan, Jiemin; Tang, Junling; Huang, Yajuan; Li, Huaping; Tao, Minfang; Liu, Fang
Abstract: Aims: The aim of this study was to assess the association between levels of alkaline phosphatase (ALP) in early pregnancy and the incidence of large-for-gestational-age (LGA) neonates in pregnant women without gestational diabetes mellitus. Methods: A prospective cohort was carried out in 544 women and their biochemical parameters including serum ALP and demographic characteristics were collected in 13–16th gestational week. At 24–28th weeks of gestation, 50 g oral glucose challenge test and oral 75 g glucose tolerance test was performed. LGA was defined as birth weight ≥ 90th percentile for completed week of gestational age based on the sex-specific growth curves. Logistic regression and receiver operating characteristic analysis were utilized to identify independent risk factors and odds ratio among ALP quartiles for incidence of LGA. Results: Women diagnosed as LGA held higher level of ALP than women in non-LGA group ( P  = 0.008). Moreover, ALP (odds ratio (OR) 1.05 [95% confidence interval (CI): 1.00, 1.10]) was the independent risk factors associated with LGA. Compared with ALP quartile 1, women in quartile 4 had more than 2.5-fold increased odds of LGA (OR 3.78, 95% CI: 1.10, 13.02), and the risk reached 4 times after adjusting several covariates (OR 4.15, 95% CI: 1.14, 15.13). Conclusions: A significantly increased risk of LGA was associated with higher serum concentrations of ALP in pregnant women with NGT, even it is in normal reference range.